Anaesthetic implications of antiphospholipid antibody syndrome in pregnancy - Priyanka Garg; Prachi Gaba; Kirti N Saxena; Bharti Taneja (Wolters Kluwer Medknow Publications, 2011)
Antiphospholipid antibody syndrome is an autoimmune disorder characterized by venous and/or arterial thromboses. When present in women of reproductive age, it is associated with recurrent loss of pregnancy. This case report summarizes the perioperative course and anaesthetic management in a patient with bad obstetrics history who had to undergo emergency caesarean section.